Konsep Kurikulum Merdeka Dalam Pendidikan - Atin Srihandayani; Meylina Astuti; Ratna Sari; Mustafiyanti Mustafiyanti (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
At the National Teacher's Day commemoration event in 2019 the Minister of Education and Culture or the Ministry of Education and Culture initiated the concept of "Free Learning Education". This concept is a response to the needs of the education system in the era of the industrial revolution 4.0, Minister Nadiem Makarim said that freedom to learn is freedom to think, freedom to think is determined by the teacher, so the main key that supports the new education system is the teacher, where the teacher is tasked with shaping the future. front of the nation. The concept of Freedom to Learn is no longer an idea but rather a policy that will be implemented. Freedom to learn is a word that is often interpreted and explained as freedom in its true sense. The point of the problem is that there are still restrictions everywhere, especially in education, educators and students cannot feel sufficient autonomy to determine the direction of policy in learning and teaching because they are still regulated by regulations which make the implementation and evaluation process plans carried out seem limited and tie. The concept of Freedom of Learning is an agreement in reconstructing the national education system, by reorganizing the education system in order to support the progress of change and progress of a nation that adapts to changing times.